Dissociative symptoms with intravenous ketamine in treatment-resistant depression exploratory observational study - Włodarczyk, Adam (Medicine (Baltimore), 2021)
There is evidence for ketamine use in treatment-resistant depression (TRD). Several safety and tolerability concerns arise regarding adverse drug reactions and specific subpopulations. This paper aims to investigate the relationship between dissociative and psychometric measures in course of intravenous ketamine treatment in TRD inpatients with major depressive disorder and bipolar disorder. This study result represents safety data in a population of 49 inpatients with major depressive disorder and bipolar disorder subjects receiving eight 0.5 mg/kg of ketamine intravenous infusions, with a duration of 40 min each, as an add-on treatment to standard-of-care pharmacotherapy, registered in the naturalistic observational protocol of the tertiary reference unit for mood disorders (NCT04226963). The safety psychometrics assessed dissociation and psychomimetic symptomatology with the Clinician-Administered Dissociative States Scale (CADSS) the Brief Psychiatric Rating Scale (BPRS). The significant differences in CADSS scores between measurements in course of the treatment were observed (P = .003). No significant differences between BPRS measurements were made after infusions. In each case, both BPRS and CADSS values dropped to the “absent” level within 1 hour from the infusion. Neither CADSS nor BPRS scores were associated with the treatment outcome. The study demonstrates a good safety profile of intravenous ketamine as an add-on intervention to current psychotropic medication in TRD. The abatement of dissociation was observed in time with no sequelae nor harm. The study provides no support for the association between dissociation and treatment outcome. This study may be underpowered due to the small sample size. The protocol was defined as a study on acute depressive symptomatology without blinding.